Parotid gland tumors: a retrospective study of 154 patients - Maahs,Gerson Schulz (2015)
INTRODUCTION: Benign tumors of the parotid gland comprise the majority of salivary gland tumors. OBJECTIVE: To review the clinical characteristics of parotid gland tumors submitted to surgical treatment by the same surgeon. METHODS: Retrospective study with 154 patients who had parotid gland tumors. Clinical and histological data, type of surgery, and complications were assessed and described. RESULTS: The main manifestation was a mass with a median evolution of 12 months for benign tumors and five months for malignant tumors. Ultrasonography was the most frequent complementary exam. Pleomorphic adenoma was the most common of the benign tumors, and mucoepidermoid carcinoma was the most frequent malignant tumor. Superficial parotidectomy with preservation of the facial nerve was the most common surgical procedure and reversible paresis of branches of the facial nerve was the most common complication. CONCLUSIONS: Pleomorphic adenoma is the most common parotid gland tumor and superficial parotidectomy with preservation of the facial nerve is the most common and appropriate treatment for most low-morbidity tumors.